2006
DOI: 10.1007/s00049-006-0354-8
|View full text |Cite
|
Sign up to set email alerts
|

Herbicide exposure affects the chemical recognition of a non native predator in common toad tadpoles (Bufo bufo)

Abstract: In amphibians and fishes, evidence is increasing that chemical cues from injured conspecifics can play a role in the chemical labelling and learned recognition of unfamiliar predators. In this laboratory study, we tested the prediction that prior chemical exposure to a non-native predator feeding on conspecific tadpoles will subsequently allow tadpoles of the common toad (Bufo bufo) to recognize the chemical cues specifically released by this starved predator. Furthermore, we investigated the vulnerability of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(20 citation statements)
references
References 40 publications
0
19
0
1
Order By: Relevance
“…Indeed with one exception, all amphibian studies of contaminants and predator-prey interactions have focused on pesticides (reviewed in . In these pesticide studies, common behavioral responses of prey to predators and contaminants together included changes in activity level (Bridges 1999a, Bridges 1999b, Relyea and Edwards 2010, decreased feeding (Broomhall 2004), failure to appropriately use refugia (Bridges 1999a), and inability to detect predators by olfactory means (Mandrillon and Saglio 2007). In several studies behavioral changes led to increased vulnerability to lethal predation (Bridges 1999b, Broomhall 2002, Broomhall 2004, Relyea and Edwards 2010.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed with one exception, all amphibian studies of contaminants and predator-prey interactions have focused on pesticides (reviewed in . In these pesticide studies, common behavioral responses of prey to predators and contaminants together included changes in activity level (Bridges 1999a, Bridges 1999b, Relyea and Edwards 2010, decreased feeding (Broomhall 2004), failure to appropriately use refugia (Bridges 1999a), and inability to detect predators by olfactory means (Mandrillon and Saglio 2007). In several studies behavioral changes led to increased vulnerability to lethal predation (Bridges 1999b, Broomhall 2002, Broomhall 2004, Relyea and Edwards 2010.…”
Section: Introductionmentioning
confidence: 99%
“…Second, Cu might interfere with olfaction, thereby altering normal predator detection and avoidance behavior. We made the following predictions about tadpole behavior: (1) Tadpoles exposed to this low concentration of Cu alone might reduce activity (Redick andLa Point 2004, Chen et al 2007) but were not expected to change their microhabitat use; (2) Tadpoles exposed to predator cues alone would reduce activity and seek refuge at the tank bottom to minimize risk of predation (e.g., Peacor 2006, Fraker 2008; and (3) Tadpoles in combined Cu and predator treatments would not detect the predator cue due to olfactory inhibition by Cu; consequently they would behave identically to animals treated with Cu alone (e.g., Mandrillon and Saglio 2007). We elected to focus this study on Cu because of its relevance as a widespread aquatic contaminant, its known toxicological effects in other studies (cited above), and because the role of metals in causing abnormalities or altering aquatic predation dynamics has not been fully considered .…”
Section: Introductionmentioning
confidence: 99%
“…all individuals re spond irrespective of whether they have been previously exposed, or induced, which means that a naive individual will not respond or will show a weaker response than an experienced individual. Effects on predator recognition have previously been demonstrated in fish and tadpoles exposed to acidification, pesticides and heavy metals (Scott et al 2003, Mandrillon & Saglio 2007. Scott et al (2003) also found that the effect of the contaminant on behaviour was only present after waterborne exposure.…”
Section: Behavioural Effectsmentioning
confidence: 88%
“…These increased contaminant levels have direct negative effects on biodiversity, but may also have indirect effects on natives by favoring an invasive species. For example, low level herbicide exposure interferes with native toad (Bufo bufo) species recognition of non-native crayfish cues (Mandrillon and Saglio 2007). Another indirect pathway favoring the invader results if it is more pollution tolerant than natives.…”
Section: Discussionmentioning
confidence: 99%